Penguatan Nilai-Nilai Antikorupsi Peserta Didik dalam Pembelajaran PPKn - Nadia Rahma Tika; Maria Montessori; Muhammad Prima Ersya (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
This study aims to equip students to instill several anti-corruption values that focus on discipline, responsibility, and honesty. The method used in this research is a qualitative research with a descriptive approach. The primary data of this research are from observations and interviews with various parties, such as: PPKn teachers, guidance and counselling teachers and vice principals. The secondary data of this research are from articles as a supporting reference for data. The results of this study reveal that strengthening the anti-corruption values of students is part of the school's commitment. The form of reinforcement is given in the form of rewards and punishments which are carried out in collaboration with PPKn teachers and BK teachers. This is proven to be able to shape the attitude of students in the aspects of discipline, responsibility, and honesty.